NEW AROMATIC BIOMARKERS IN SULFUR-RICH COAL - Gorchs R.; Olivella M.A.; De Las Heras F.X.C. (My University, 2003)
A molecular study of linear, branched and isoprenyl alkylbenzene skeletons and alkenylbenzenes in the soluble fraction extracted from a sulfur-rich Utrillas coal was carried out using gas chromatography-mass spectrometry (GC-MS). The presence of C24-C28 diaromatic compounds, not previously reported in coals, suggests that photosynthetic green sulfur bacteria may have made an input of organic matter to these coals. The unsaturated linear alkenylbenzenes and isoprenyl (C15 and C20) alkylbenzene skeletons are also described for the first time in the soluble fraction of geological samples.